Principals’ Challenges to Implement School Based Management in English-Speaking Schools Setting - Mario Nugroho Willyarto; Anggaripeni Mustikasiwi (Bina Nusantara University, 2020)
The aim of the research was to identify and map the school principals’ competence in English-speaking schools setting, according to the Decree of Ministry of Education no 13/2007 regarding competence standard for school principals and in implementing school-based management (SBM). The research applied a qualitative descriptive method, although the data were processed in a quantitative way. The data were gathered through structured questionnaires collected from ten principals and 74 teachers from ten schools. Data validation was conducted through interviews with ten school principals, two teachers per school, and the board’s representatives. The result of the research is the recommendations of the school principals’ competence development program as an alternative solution for the schools. The result shows that the school principals’ competencies have met the government standard competence. In the implementation of SBM, the school principals need to improve their five dimensions of principal competence (personal, managerial, entrepreneurship, supervision, and social). Especially the essence of SBM through training programs are principals’ roles and responsibilities, developing school profiles, school visioning, financial and school facilities management, strategic planning, school as a learning community, academic supervision, monitoring and evaluation, school marketing and branding, and nontraining programs.